2012
DOI: 10.5367/te.2012.0148
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Income and Economic Growth in Greece: Empirical Evidence from Their Cyclical Components

Abstract: This paper examines the relationship between the cyclical components of Greek GDP and international tourism income for Greece for the period 1976-2004. Using spectral analysis the authors find that cyclical fluctuations of GDP have a length of about nine years and that international tourism income has a cycle of about seven years. The volatility of tourism income is more than eight times the volatility of the Greek GDP cycle. VAR analysis shows that the cyclical component of tourism income is significantly inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 62 publications
5
52
1
1
Order By: Relevance
“…It is thus surprising that, according to the directional spillovers, the relationship between the Greek tourism sector and the national economy is not very strong until 2006 (see Figure 5). This contradicts the findings from previous studies which suggest a strong link between the two variables (Dritsakis, 2012;Eeckels et al, 2012). Between 2006 and 2008 we observe that tourism growth has an increasing effect towards economic growth, while the exact reverse behaviour is observed for economic growth to tourism growth.…”
Section: Greececontrasting
confidence: 99%
See 1 more Smart Citation
“…It is thus surprising that, according to the directional spillovers, the relationship between the Greek tourism sector and the national economy is not very strong until 2006 (see Figure 5). This contradicts the findings from previous studies which suggest a strong link between the two variables (Dritsakis, 2012;Eeckels et al, 2012). Between 2006 and 2008 we observe that tourism growth has an increasing effect towards economic growth, while the exact reverse behaviour is observed for economic growth to tourism growth.…”
Section: Greececontrasting
confidence: 99%
“…In particular, it is believed that tourism (i) increases foreign exchange earnings, which in turn can be used to finance imports (McKinnon, 1964), (ii) it encourages investment and drives local firms towards greater efficiency due to the increased competition (Krueger, 1980;Balaguer and Cantavella-Jorda, 2002), (iii) it alleviates unemployment, since tourism activities are heavily based on human capital (Brida and Pulina, 2010) and (iv) it leads to positive economies of scale thus, decreasing production costs for local businesses (Andriotis, 2002;Croes, 2006). Other recent studies which find evidence in favour of the TLEG hypothesis include Sugiyarto et al (2003), Durbarry (2004), Parrilla et al (2007), Croes and Vanegas (2008), Proenca and Soukiazis (2008), Fayissa et al (2011), Pratt (2011), Dritsakis (2012), Eeckels et al (2012), Ivanov and Webster (2013), Surugiu and Surugiu (2013).…”
Section: Introductionmentioning
confidence: 98%
“…This is consistent to evidences in Italy (Brida et al, 2010), Tunisia (Cortés-Jiménez et al, 2011) and Greek (Eeckels et al, 2012). Consequently, the findings support the tourism-led economic growth hypothesis and are of particular interest and importance to policy makers, financial analysts and investors dealing with the tourism industry Tourism sector plays an important role in the economic development.…”
Section: Jurnal Ekonomi Pembangunan Issn 1411-6081 E-issn 2460-9331supporting
confidence: 89%
“…Since then, the first paper that formally confirmed the tourism-led growth hypothesis through cointegration and causality tests for the case of the Spanish economy was published in 2002 (Balaguer & Cantavella-Jordá, 2002). Several other time series studies showing the relationship between tourism and economic growth reported a long run equilibrium relationship and evidence for causality among the variables of interest specifically for southern European Mediterranean countries (Cortés-Jiménez & Pulina, 2010;Dritsakis, 2004;Eeckels, Filis, & Leon, 2012;Gunduz & Hatemi-J, 2005;Katircioglu, 2007;Kim, Chen, & Jang, 2006;Massidda & Mattana, 2013;Nowak, Sahli, & Cortés-Jiménez, 2007).…”
Section: Brief Review Of Earlier Studiesmentioning
confidence: 89%